2015
DOI: 10.1016/j.solmat.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

From simulation to experiment: Understanding BO-regeneration kinetics

Abstract: a b s t r a c tRegeneration of boron oxygen related defects is investigated in differently compensated silicon wafers. It is shown for the first time that boron oxygen defects can be transformed into a stable regenerated state also in compensated n type silicon.The coupling between regeneration rate and the completeness of the regeneration reaction is simulated based on the 3 state model of BO defects. Maximum regeneration temperatures that can be applied are determined for differently regenerating samples. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The impact of the BO related-defect has been extensively studied in p-type boron doped and compensated silicon, as well as in n-type compensated silicon for several years. 8,10,19,20 Recently, the focus has moved to the permanent deactivation of the BO defects [21][22][23][24][25] by annealing under Munzer 21 and Herguth et al 22 reported regeneration of the BO defect in p-type silicon solar cells at 50 to 75 C, and showed that the regenerated cells had similar V oc and efficiencies as the cells before degradation. The cells were stable under illumination of 1 sun intensity over 200 h. However, from Figure 5, it can be seen that the V oc of the regenerated cells cannot be recovered to the initial value.…”
mentioning
confidence: 99%
“…The impact of the BO related-defect has been extensively studied in p-type boron doped and compensated silicon, as well as in n-type compensated silicon for several years. 8,10,19,20 Recently, the focus has moved to the permanent deactivation of the BO defects [21][22][23][24][25] by annealing under Munzer 21 and Herguth et al 22 reported regeneration of the BO defect in p-type silicon solar cells at 50 to 75 C, and showed that the regenerated cells had similar V oc and efficiencies as the cells before degradation. The cells were stable under illumination of 1 sun intensity over 200 h. However, from Figure 5, it can be seen that the V oc of the regenerated cells cannot be recovered to the initial value.…”
mentioning
confidence: 99%
“…20 In addition, some recent results showed the long-time stability of the permanent deactivation of BO defects in compensated n-Si. 22,24 Combining the modelling results of the charge states, the authors attributed the binding of H and BO defects to covalent binding rather than an ionic interaction. 22…”
Section: B the Reactants' Charge States In The Hydrogenation Of Fe Imentioning
confidence: 98%
“…22,24 Combining the modelling results of the charge states, the authors attributed the binding of H and BO defects to covalent binding rather than an ionic interaction. 22…”
Section: B the Reactants' Charge States In The Hydrogenation Of Fe Imentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing the defect formation rate at a given temperature also increases the effectiveness of LID mitigation during illuminated annealing processes (the ratio of passivated to inactive defects). Higher defect formation rates enable the use of higher processing temperatures without sacrificing the effectiveness of LID mitigation [89,93]. The increased temperatures can lead to a further acceleration of the processes due to the exponential dependence of the reaction rates on processing temperature as well as the increase in carrier concentrations and lifetime at higher temperatures [133,135].…”
Section: Role Of Defect Formationmentioning
confidence: 99%